2011
DOI: 10.1007/s00403-011-1182-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridisation analysis of keloid tissue in Caucasians suggests possible involvement of HLA-DRB5 in disease pathogenesis

Abstract: Keloid disease (KD) is a common fibroproliferative disorder that can occur following cutaneous injury in genetically susceptible individuals. Familial predisposition, high prevalence in certain populations and occurrence in twins suggest a strong genetic component to KD. However, to date no single causative gene has been identified. Copy number variations (CNVs) in genes have been associated with several human diseases including common skin disorders. The objective of this study was, therefore to determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…Here, we found that CNVS of HLA-DRB5 was associated with SLE disease susceptibility. A recent study has revealed the involvement of HLA-DRB5 CNVS in the development of Keloid disease through minor puncture wounds in Caucasians [17]. For the first time, we discovered that HLA-DRB5 CNVS was genetically associated with SLE in Han Chinese.…”
Section: Discussionmentioning
confidence: 82%
“…Here, we found that CNVS of HLA-DRB5 was associated with SLE disease susceptibility. A recent study has revealed the involvement of HLA-DRB5 CNVS in the development of Keloid disease through minor puncture wounds in Caucasians [17]. For the first time, we discovered that HLA-DRB5 CNVS was genetically associated with SLE in Han Chinese.…”
Section: Discussionmentioning
confidence: 82%
“…Due to familial tendency to develop keloids, for several years several genetic factors have been discussed (e.g. genes regulating apoptosis, mitogen‐activated protein kinase, TGF‐β signal cascade, interleukin‐6, plasminogen activator inhibitor‐1) [10].…”
Section: Biological Aspects Of Wound Healing and Scar Formationmentioning
confidence: 99%
“…In addition, the human leukocyte antigen (HLA) system has been demonstrated to be a crucial factor in keloid pathogenesis among various ethnic groups. Previous studies on Caucasians have indicated that a positive association exists between the HLA-DRB1*15 allele and keloid susceptibility [8], and that the HLA-DRB5 copy number is associated with keloid development at sites of minor puncture wounds [37]. In addition, the HLA-DQA and DQB alleles have been reported to be associated with keloid susceptibility in ethnic Chinese populations [28].…”
Section: Introductionmentioning
confidence: 98%